The First Decade of Web-Based Sports Injury Surveillance: Descriptive Epidemiology of Injuries in US High School Boys' Ice Hockey (2008-2009 Through 2013-2014) and National Collegiate Athletic Association Men's and Women's Ice Hockey (2004-2005 Through 2013-2014) - Lynall, R. C.; Mihalik, J. P.; Pierpoint, L. A.; Currie, D. W.; Knowles, S. B.; Wasserman, E. B.; Dompier, T. P.; Comstock, R. D.; Marshall, S. W.; Kerr, Z. Y. (Journal of Athletic Training, 2018)
Context Web-based sports injury surveillance via programs such as the High School Reporting Information Online system and the National Collegiate Athletic Association Injury Surveillance Program has aided efforts to collect data on ice hockey injuries.